STRATEGI PEMBELAJARAN UNTUK MENGATASI SISWA YANG MENGALAMI KESULITAN BELAJAR DISLEKSIA - Devi Nurajijah, - (2020)
Dyslexia learning difficulties are a student problem that must be considered by the teacher, or parents. Dyslexia students must be detected as early as possible in order to be overcome, properly and in finding the right solution. Students who have difficulty learning dyslexia will, experience things that become distractions for themselves during the learning process, and this will be a danger if left unchecked. Both teachers and parents must be able to recognize the characteristics of students who have difficulty learning dyslexia, then find out the factors causing these difficulties. After knowing these two things, there needs to be a strategy used to overcome the learning difficulties of dyslexic students, which of course is not easy to guide it requires patience and is done gradually.The purpose of this study is to: (1) Explain the characteristics of dyslexic student learning difficulties, (2) Explain the factors that cause dyslexic learning difficulties, (3) Explain the strategies or methods used in overcoming dyslexia learning difficulties.The approach used in this research is a qualitative approach, with the research method being Literature Study or Literature Study. Due to the existence of Covid - 19 which makes researchers have difficulty in retrieving data, therefore researchers are looking for sources from literature in the form of Books, Journals, Articles, Previous Thesis, and also a Thesis that is relevant to research.Research results are presented from several journals, articles, theses and also a thesis that has been analyzed by researchers to obtain data on findings, can be seen from several strategies or methods used that are very diverse. This is where the role of the teacher in overcoming learning difficulties dyslexia is needed, a teacher must be able to guide students who experience dyslexia. The method they used on average was successful even though it was done in stages. Whether or not the strategy or method is used successfully is not a problem, the most important thing is students who have difficulty learning dyslexia must be handled specifically, requiring more attention compared to other normal students